THE STUDY OF HORTICULTURAL ATTRIBUTES OF SELECTED MEDICINAL PLANTS OF KHANPUR VALLEY IN THE SUB HIMALAYAN MOUNTAINS OF - PAKISTAN; S. M. Khan; N. Amin; H. Ahmad (Journal of Animal and Plant Sciences, 2015)
-1 -2 -1 Data was recorded on plant height, leaves plant , stem diameter, leaf dry weight, plants meter , yield plant , yield -2 -1 meter and yield hectare for three selected medicinal plants of Khanpur valley (Adhatoda vasica, Calotropis procera and Recinus communis) at their natural habitats at four selected sites and two seasons during 2013. Significant effects were observed at different seasons and sites upon various horticultural attributes of all three medicinal plants. Adhatoda -2 -2 vasica showed significantly higher values for plants meter (0.18) at Mang during summer, yield meter (10.28g) at Mang during summer and yield hectare (102.76kg) at Mang during summer. Recinus communis revealed higher values for yield hectare (248.82kg) at Mang during summer followed by Dam site during summer (220.55kg). Calotropis procera revealed higher values for yield hectare (530.02kg) at Mang during summer followed by Dabola site during summer (367.67kg). It was concluded that medicinal plants under study gave maximum yield during summer (last week of July) showed maximum yield at Mang site. Therefore, medicinal plants may be collected during last week of July for best yield. 1. To determine the annual yield for sustainable harvest
Keywords: Horticultural attributes; medicinal plants; Khanpur valley.